A KILAU SEHAT : KREATIVITAS INOVATIF MEMANFAATKAN LAHAN DAN TANAMAN UNTUK KESEHATAN - Dwi Aryani, Wulan (Bapelitbang Kabupaten Batang, 2024)
SMP Negeri 1 Kandeman has a very large area of land that needs to be optimized. Taking advantage of this situation, the school implements the